Implementation of the Rasailah Daku Program According to Street Children Beneficiaries - Stellina Shakira; Rizki Syafril (Al-Qalam Institue, 2025)
This study aims to determine the implementation of the Rasailah Daku program from the perspective of street children as beneficiaries, particularly in improving their psychosocial well-being and independence. The research method used was qualitative with a descriptive approach. Data were obtained through in-depth interviews, participant observation, and documentation of street children participating in the program and field facilitators. The results show that the Rasailah Daku program has a positive impact on increasing street children's self-confidence, self-awareness, and social skills. However, limited resources and continuity of support remain major challenges in achieving optimal results. The implications of this study highlight the importance of strengthening the capacity of facilitators, cross-sectoral support, and developing sustainable policies to ensure similar programs can provide long-term benefits for street children.